(untitled) - Yagelski, Robert (Australia, 2015)
Writing: ten core concepts is designed to help you acquire the fundamental understanding that you need to become an effective writer-and to give you practice in applying Ten Core Concepts across different writing tasks. Handy ten-step writing guides help you focus on the important questions for each of the Core Concepts in particular types of writing. Emphasizing writing as an interaction between a writer and a reader, this book offers you guidance in three main aims of writing and a way to participate in the conversations that shape our lives.
Keywords: English language,Tiếng Anh; Style,Phong cách